2017
DOI: 10.24246/j.sw.2017.v33.i1.p29-36
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Lingkungan Sebagai Sumber Pembelajaran Mata Pelajaran Ips

Abstract: <p>Mata pelajaran IPS merupakan suatu mata pelajaran yang menggunakan pendekatan terpadu yang didalamnya memadukan empat bidang kajian yaitu ekonomi, sosiologi, geografi dan sejarah. Pembejaran terpadu dimaksudkan untuk memberikan pengalaman yang bermakna kepada peserta didik dan dalam penyampaiannya guru memilih tema atau topik tertentu, pendekatan pembelajaran ini memungkinkan peserta didik baik secara individual maupun kelompok aktif mencari, menggali dan menemukan konsep serta prinsip secara holistik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
0
15
0
17
Order By: Relevance
“…Through the values contained in social studies education will provide provisions for students to develop themselves in their lives because social studies education equips students with knowledge, skills, attitudes, and values to make students who can become human beings who have an identity who can live in a peaceful society, and can provide benefits to others (Nasih et al, 2019). It is also similar to the objectives of social studies education in the 2013 curriculum, character education in the 2013 curriculum aims to improve the quality of the process and results of improving education, which leads to the formation of character and noble character of students as a whole, integrated and balanced, following competency standards for graduates of each education unit (Syaharuddin & Mutiani, 2020).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Through the values contained in social studies education will provide provisions for students to develop themselves in their lives because social studies education equips students with knowledge, skills, attitudes, and values to make students who can become human beings who have an identity who can live in a peaceful society, and can provide benefits to others (Nasih et al, 2019). It is also similar to the objectives of social studies education in the 2013 curriculum, character education in the 2013 curriculum aims to improve the quality of the process and results of improving education, which leads to the formation of character and noble character of students as a whole, integrated and balanced, following competency standards for graduates of each education unit (Syaharuddin & Mutiani, 2020).…”
Section: Resultsmentioning
confidence: 94%
“…Learning resources used in the social studies learning process will also be more accessible for students to understand if they use the surrounding environment as a learning resource (Widiastuti, 2017). In this case, it fits for teachers to add more innovations in learning resources because students are a significant input component in education to become qualified individuals and follow national education goals (Syaharuddin & Mutiani, 2020).…”
mentioning
confidence: 99%
“…It was found that students were more enthusiastic and familiar with local culture, students' interest and passion for learning had increased, teachers and books were no longer the primary learning source. [6] The success of social studies learning when contextualizing social culture has been proven in several studies; it was found that students were more enthusiastic and familiar with local culture, students' interest and passion for learning had increased, teachers and books were no longer the primary sources of learning. [6] [7] The diverse cultural diversity of Indonesia, which is diverse, needs sorting and selection of Indonesian culture because learning at Madrasah Ibtidaiyah is Islamic.…”
Section: Introductionmentioning
confidence: 99%
“…With the existence of learning resources based on local wisdom (local business) which hopefully can increase learning knowledge in life. Local businesses are also classified as industrial businesses, which are a group of industries that depend for their survival on businesses that are run on a limited local market, and are relatively scattered in terms of location [5].…”
Section: Introductionmentioning
confidence: 99%